1982
DOI: 10.1007/bf01415126
|View full text |Cite
|
Sign up to set email alerts
|

Beta-delayed neutron emission from93?100Rb to excited states in the residual Sr isotopes

Abstract: Beta-delayed neutron emission from the precursors 93-1~176 to excited states in the residual nuclei 92-998r has been measured by means of 7-ray and neutron spectroscopy. In general, considerable neutron feeding of excited final states is observed. The experimental branching ratios (P,~) are compared to predictions from statistical model calculations. It is demonstrated that the main parameter affecting the Pj-values is the shape of the/3-strength function (Sp). For several Rb isotopes hindrance, respectively e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
20
0

Year Published

1983
1983
2015
2015

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 44 publications
(24 citation statements)
references
References 40 publications
3
20
0
Order By: Relevance
“…Moreover, as discussed in Refs. [80,81,82], high-resolution spectroscopic studies of β-delayed neutron-emitter nuclei produced by fission showed that E βn was always much lower than Q β − S n (e.g. 199 keV for 87 Br, 450 keV for 98 Rb, and 579 keV for 137 I).…”
Section: Neutron Detection Efficiencymentioning
confidence: 99%
“…Moreover, as discussed in Refs. [80,81,82], high-resolution spectroscopic studies of β-delayed neutron-emitter nuclei produced by fission showed that E βn was always much lower than Q β − S n (e.g. 199 keV for 87 Br, 450 keV for 98 Rb, and 579 keV for 137 I).…”
Section: Neutron Detection Efficiencymentioning
confidence: 99%
“…[4,5] and for later compilations [36,37]), in the early 1970's the focus was more directed to measuring energy spectra of fission-product nuclei by using different types of detectors (see, e.g. the review article of Kratz in [5], and [6,7,8,9,10,11,12,13,14,15,16]. As already mentioned in the introduction, among the most common experimental methods for β dn-spectroscopy was the use of 3 He filled proportional counters or ionization chambers.…”
Section: High-resolution Spectroscopy Of β -Delayed Neutronsmentioning
confidence: 99%
“…The partial spectrum to the first excited state was obtained from a nγ-coincidence measurement with the γ-gate set on the 837 keV line (2 + 1 → 0 + ) in the final nucleus. The partial spectrum to the ground state was derived by subtracting all nγ-coincidence spectra weighted according to their integral P i n branching ratios [15]. By comparing the well resolved peaks in the singles neutron spectrum (upper left part of Fig.…”
Section: High-resolution Spectroscopy Of β -Delayed Neutronsmentioning
confidence: 99%
See 2 more Smart Citations